Critical Thinking in Arithmetic: Insights from Qur’an-Memorizing Students - Muhammad, Rosida Rakhmawati; Hanifah, Banar; Azzahra, Siti; Fahmoza, Siti Hanny; Anggoro , Bambang Sri (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
This study aims to examine the categories of Qur’an-memorizing students in relation to their critical thinking ability when solving Higher-Order Thinking Skills (HOTS) problems, particularly in arithmetic. The significance of this research lies in understanding the relationship between Qur’an memorization—an activity that strengthens memory capacity—and students’ critical thinking skills, which are essential for solving complex mathematical problems. This study explores whether Qur’an memorization can support the development of higher-order skills such as analysis and evaluation, which are crucial in mathematics learning. A descriptive qualitative approach was employed using HOTS test items and semi-structured interviews as instruments for data collection. Thematic analysis was applied to identify possible relationships among students’ critical thinking ability, arithmetic problem-solving performance, and Qur’an memorization practices. The findings revealed that students in the high Qur’an memorization category exhibited less consistent performance in solving HOTS problems compared to those in the moderate and low categories. This suggests that while Qur’an memorization may enhance certain aspects of critical thinking, it does not necessarily guarantee proficiency in solving higher-order mathematical problems. The study provides new insights into how faith-based learning practices may influence students’ cognitive development in mathematics and contribute to a broader understanding of the interaction between religious education and higher-order cognitive skills.